Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1038/15996
|View full text |Cite
|
Sign up to set email alerts
|

G-protein-independent signaling mediated by metabotropic glutamate receptors

Abstract: Synaptically released glutamate activates ionotropic and metabotropic receptors at central synapses. Metabotropic glutamate receptors (mGluRs) are thought to modulate membrane conductances through transduction cascades involving G proteins. Here we show, in CA3 pyramidal cells from rat hippocampus, that synaptic activation of type 1 mGluRs by mossy fiber stimulation evokes an excitatory postsynaptic response independent of G-protein function, while inhibiting an afterhyperpolarization current through a G-prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 48 publications
7
123
2
Order By: Relevance
“…In the context of NMDAR-mediated neurotransmission, the mGluR5 subtype of mGluRs is of special interest. The mGluR5 binds through G-dependent or independent pathways (Heuss et al, 1999) with predominantly couple via Gq to phospholipase C. This yields diacylglycerol, which activates protein kinase C (PKC), and inositol-1,4,5-triphosphate, which releases intracellular Ca 2 + (Conn and Pin, 1997), and this in turn can increase NMDAR-evoked responses in a variety of neuronal tissues (Doherty et al, 1997;Awad et al, 2000), indicating one potential functional link between mGluR5 and NMDAR. Indeed, administration of mGluR5 antagonist 2-methyl-6-(phenylethynyl)pyradine (MPEP) facilitated in vivo effects of NMDAR antagonists in rodents, producing anxiolytic (Spooren et al, 2000), neuroprotective (Bruno et al, 2000), and anticonvulsant (Chapman et al, 2000) effects, disrupting prepulse inhibition (PPI) (Kinney et al, 2003) and enhancing the detrimental effects of MK-801 on cognition and stereotypy (Homayoun et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of NMDAR-mediated neurotransmission, the mGluR5 subtype of mGluRs is of special interest. The mGluR5 binds through G-dependent or independent pathways (Heuss et al, 1999) with predominantly couple via Gq to phospholipase C. This yields diacylglycerol, which activates protein kinase C (PKC), and inositol-1,4,5-triphosphate, which releases intracellular Ca 2 + (Conn and Pin, 1997), and this in turn can increase NMDAR-evoked responses in a variety of neuronal tissues (Doherty et al, 1997;Awad et al, 2000), indicating one potential functional link between mGluR5 and NMDAR. Indeed, administration of mGluR5 antagonist 2-methyl-6-(phenylethynyl)pyradine (MPEP) facilitated in vivo effects of NMDAR antagonists in rodents, producing anxiolytic (Spooren et al, 2000), neuroprotective (Bruno et al, 2000), and anticonvulsant (Chapman et al, 2000) effects, disrupting prepulse inhibition (PPI) (Kinney et al, 2003) and enhancing the detrimental effects of MK-801 on cognition and stereotypy (Homayoun et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, activation of this current was not blocked by GDPβS or GTPγS, indicating that G-proteins were not required to couple activation of the mGlu receptor to its effector (Guérineau et al 1995). Rather, activation of this Group I mGlu receptor current depends on Src family protein tyrosine Kinases (Heuss et al 1999). Using the selective agonist DHPG, Gee et al (2003) showed that activation of Group I mGlu receptors in CA3 can also activate cation currents in a G-protein and Ca 2+ -dependent manner.…”
Section: Trpc Channelsmentioning
confidence: 98%
“…The involvement of G proteins can be tested with GDPβS or GTPγS. These non-hydrolysable GTP analogs nonselectively inactivate or hyperactivate, respectively, Gprotein-mediated pathways (Heuss et al 1999). Selective inhibition of Gα i or Gα q can be achieved with pertussis toxin (PTX) and UBO-QIC, respectively (Schrage et al 2015), although these two drugs will also affect Gβγ functions (Gao and Jacobson 2016).…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…mGlu1 and mGlu5 receptors are thought to couple through Gq-type G-proteins to phospholipase C (PLC)-b, which results in intracellular Ca 2C mobilization via inositol (1,4,5)-trisphosphate (IP 3 ) and ryanodine receptors (Fagni et al, 2000;Stefani et al, 1996). Group I mGlu receptors have also been implicated in a variety of alternative intracellular transduction pathways, including adenylyl cyclase (Aramori and Nakanishi, 1992), tyrosine kinase (Heuss et al, 1999), mitogen-activated protein kinase and phosphoinositide 3-kinase (Rong et al, 2003).…”
Section: Introductionmentioning
confidence: 99%